Effectiveness and tolerability of rimegepant in the acute treatment of migraine: a real-world, prospective, multicentric study (GAINER study) - Luigi Francesco Iannone; Gloria Vaghi; Gabriele Sebastianelli; Francesco Casillo; Antonio Russo; Marcello Silvestro; Francesca Pistoia; Giorgio Dalla Volta; Matteo Cortinovis; Alberto Chiarugi; Danilo Antonio Montisano; Maria Pia Prudenzano; et al. (The Journal of Headache and Pain)
Abstract Background Rimegepant, a novel oral calcitonin gene-related peptide receptor antagonist, has been recently approved for the acute migraine treatment. While its efficacy was confirmed in randomized clinical trials, no data is available regarding real-life effectiveness and tolerability. GAINER, a prospective, multicentric study, aimed to evaluate rimegepant effectiveness and tolerability in the real-world setting. Methods Our study involved 16 headache centers across Italy. The main outcomes were: i) 2 h pain freedom, and ii) occurrence of treatment-emergent adverse events after administration. Participants were instructed to treat one migraine attack with rimegepant 75 mg orally disintegrating tablet. Using an ad hoc diary, participants prospectively collected migraine attack features at baseline and every 30 min after rimegepant administration, up to 2 h post dose. A 24 h follow up was also collected. Results We enrolled 103 participants with migraine (74.8% female, mean age 44.4 [42.0 – 46.7] years, 24.3% with chronic migraine of whom 44.0% presented a concomitant diagnosis of medication overuse headache). The number of previously failed preventive classes was 2.7 [2.3 – 3.2]. Participants presented a mean of 9.6 [8.2 – 10.9] monthly migraine days at baseline. At rimegepant intake, 40.8% of patients rated migraine intensity as severe. Pain freedom 2 h post dose was reported in 44.7% (46/103) of individuals. Pain freedom 2 h post dose was not influenced by baseline pain severity (p = 0.316), but it was associated with timing of intake (p = 0.032) with a higher rate of 2 h pain freedom when rimegepant was taken within 1 h from pain onset. Mild adverse events were reported in 15.5% total attacks (16/103), predominantly fatigue (n = 6), gastrointestinal symptoms (n = 6), somnolence (n = 4), and transient cognitive difficulties (n = 3). Tolerability was rated as good-to-excellent in 85.4% cases (88/103). Conclusions Our data confirms rimegepant effectiveness and safety in the acute migraine treatment in a real-world setting in a cohort of participants that includes subjects with episodic or chronic migraine, medication overuse and a high number of prior preventive treatment failures. Trial registration The study was preregistered on clinicaltrial.gov, NCT05903027.